MANAGEMENT OF EDUCATIONAL RESOURCES AS PREDICTORS OF SECONDARY SCHOOL EFFECTIVENESS IN CALABAR EDUCATION ZONE OF CROSS RIVER STATE, NIGERIA (UNIZIK Journal of Educational Management and Policy, 2024)
This study investigated management of educational resources as predictor of secondary schooleffectiveness in Calabar Education Zone of Cross River State, Nigeria. The research design adopted inthis study was a correlation design. The population and sample of this study were 97 and 50 publicsecondary school respectively. An instrument for data collection was developed by the researcher andwas entitled; “Management of Educational Resource and Secondary School EffectivenessQuestionnaire (MERSSEQ)” To establish the reliability of the instrument, the researchersadministered a test 50 teachers who were not involved in the study. The reliability indices of theinstrument ranged from 0.82 to 0.88, As such, the instrument was justified suitable to be used for datacollection. The data collected were coded and analyzed using simple linear regression. The result ofthe analysis indicated that management of educational resources in terms of physical and humanresources significantly predict secondary school effectiveness in such areas as monitoring ofstudents’ academic progress and conducive teaching and learning environment Calabar EducationZone of Cross River State. Based on the results of the analysis, one of the recommendations was that,principals of public secondary schools should ensure improvement in the management of theirrespective schools’ physical resources in order to enhance secondary school effectiveness in the areaof provision conducive learning environment for effective teaching and learning processes.
Keywords: Educational Resources, Physical Resources, Human Resource, Effectiveness